PENGARUH PENGEMBANGAN KARIER DAN MOTIVASI TERHADAP PROMOSI JABATAN DAN KINERJA PEGAWAI DI BADAN PEMBERDAYAAN MASYARAKAT KABUPATEN SAMPANG - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
The purpose of this study was to analyze and examine the effect of career development and motivation on promotion and employee performance at the Community Empowerment Agency of Sampang Regency. The research method used is quantitative method, with a sample of 57 employees. The results showed that effect of career development and motivation on employee performance is significant, effect of career development and motivation on promotion is significant, effect of promotion on employee performance is significant, and job promotions are able to improve employee performance and effect of career development and motivation on job promotion and employee performance are significant.